Review on Characteristics and Typical Control Strategies of Electro-hydraulic Position Servo Systems Based on Complex Working Conditions - Li, Jianying; Jiang, Liqun; Wang, Zhao (Recent Patents on Engineering, 2025)
BackgroundElectro-hydraulic position servo system is widely used, in order to cope with complex working conditions, the system is required to have high dynamic response and accurate position control ability, while the characteristics of the system and its control strategy need to be studied in depth.ObjectiveTo review the characteristics of electro-hydraulic position servo systems and typical control strategies under complex working conditions, and summarize their advantages and disadvantages to provide a basis for the design and optimization of electro-hydraulic position servo systems.MethodsLiterature and patents related to electrohydraulic position servo system characteristics and control strategies are collected, synthesized and summarized.ResultsThe characteristics of electro-hydraulic position servo system under complex working conditions are summarized, especially the performance of the system and the application effect of the control strategy under the working conditions such as load disturbance and gap nonlinearity. In addition, the application of sliding mode control, adaptive control and neural network control in electrohydraulic servo systems is summarized.ConclusionIn different complex working conditions, the selection of appropriate control strategies can improve the performance and stability of electro-hydraulic position servo systems. The study of the characteristics of electro-hydraulic position servo systems and typical control strategies is of great significance to the development of electro-hydraulic position servo systems.
Keywords: sliding mode control